(untitled) (Archives of Pediatrics of Uruguay, 2023)
Introduction: viral acute respiratory infections are usually more frequent and severe in children than in adults. However, in the case of COVID-19, most pediatric cases are mild or asymptomatic. Objective: describe the clinical and epidemiological characteristics of children with COVID-19 assisted by a health provider in Montevideo, during the first year of the pandemic. Materials and methods: retrospective descriptive study. Sample: patients under 15 years of age with positive RT-PCR for SARS-CoV-2 between 3/13/2020-03/31/2021. Main variables: symptomatology, comorbidities, epidemiological link and generation of secondary cases. Results: 6,642 RT-PCR tests were performed for SARS-CoV-2, 486 positive (7%). 94% were diagnosed between 12/2020 and 3/2021. Respiratory symptoms were the most frequent in 98% of symptomatic cases. 60% had fever. 94% had had contact with a confirmed case of COVID-19, 57% intra-domiciliary, 31% at educational centers, and 10% got infected during social activities. 86% of the contacts were adults. Two hundred and fifteen children were the initial case at the household and 73 (34%) generated secondary intra-domiciliary cases. Conclusions: the results describe the clinical and epidemiological situation of a pediatric population in Montevideo during the first year of the pandemic. Given the constant changes in the transmission dynamics and cases, it is necessary to continue to monitor and perform this type of study to adjust the definitions of suspected cases and rationalize testing prescriptions.